Teologi Islam dan Kosmologi: Penciptaan Alam Semesta Menurut Al-Qur'an, Konsep Multiverse, dan Hubungan Teori Evolusi dengan Ajaran Islam dalam Perspektif Sains Modern - Dina, Dina Wilda Sholikha; Anwar, Najih; Anwar, Sofiatul Mahmudah; maajid, aunur shabur maajid amadi (Indo-MathEdu Intellectuals Journal, 2024)
The development of modern science, particularly in cosmology and evolutionary biology, raises questions about how Islamic theology can engage in dialogue with contemporary scientific theories such as the Big Bang theory, the multiverse concept, and the theory of evolution. The objective of this research is to explore Islamic theology and cosmology, focusing on the aspects of the Creation of the Universe according to the Qur'an, the Multiverse Concept, and the Relationship between Evolutionary Theory and Islamic Teachings from the perspective of modern science. The method used in this study is a Systematic Literature Review by analyzing previous relevant studies on Islamic theology and cosmology. The findings show a connection between Islamic theology and the science of the creation of the universe, the multiverse, and evolutionary theory. The Qur'an presents creation as the will of God, encompassing both physical and spiritual dimensions. The concept of the multiverse is acceptable as long as it does not contradict the oneness of God (tawhid), while the theory of evolution is understood as part of the divine plan. Dialogue between theology and science enriches our understanding of the cosmos and opens up opportunities for relevant interdisciplinary research.